Performance of Planting Tools (Seed Planter) on Rice Land, Palu City, Central Sulawesi - ANUGERAH FITRI AMALIA; Syafruddin (Jurnal Agritechno, 2022)
The application of innovation and technology in agricultural machinery in the world is one of the factors in increasing production and productivity of agricultural products. One of them is the application of agricultural machinery, namely the process of planting on agricultural land. The use of agricultural machinery at the farm level, especially planting, is still rarely carried out, as long as the availability of agricultural labor is decreasing. Most agricultural workers have entered non-productive age, while the interest of the younger generation to enter the world of agriculture is getting lower, especially conventional agriculture. Agricultural mechanization can solve this problem. The purpose of this research is to produce the performance of the seed planter in lowland rice fields. The research method uses an agrotechnical study that measures the theoretical capacity (Kt), actual working capacity (Ka), the efficiency of the seed planter's performance, and wheel slip on the seed planter. Based on the test results the average field capacity performance is 1.301 ha/hour, the test results are the actual average field capacity 0.650 ha/hour, the test results are the average efficiency of the tool performance is 50.0%, and the average slip test results wheel that is 13.75%. Factors that affect the performance test of planting tools, among others: operator skills, soil conditions, wheel slip, shape and size of planting tools, as well as the topography of a land. Keywords: Actual Work Capacity (Ka), Theoretical Work Capacity (Kt), Efficiency, Wheel Slip, Seed Planter